Dyschromatosis ptychotropica: an unusual pigmentary disorder in a boy with epileptic encephalopathy and progressive atrophy of the central nervous system$da novel entity? - Helbig, Ingo; Fölster-Holst, Regina; Brasch, Jochen; Haußer-Siller, Ingrid; Baalen, Andreas van; Muhle, Hiltrud; Alfke, Karsten; Caliebe, Almuth; Stephani, Ulrich; Happle, Rudolf (European journal of pediatrics, 2010)
The skin and the central nervous system are tissues of common ectodermal origin and share a close ontogenetic relationship. Genetic diseases primarily affecting both organ systems are regularly encountered in both dermatological and neurological settings. Here, we report on a boy with epileptic encephalopathy, severe intellectual disability, optic atrophy, and progressive cerebellar and supratentorial atrophy, reminiscent of progressive encephalopathy with edema and hypsarrythmia (PEHO) syndrome displaying a previously undescribed dyschromatosis in the form of progressive reticulate and mottled hyper- and hypopigmentation of the neck and the inguinal and axillary regions. We hypothesised that this combination of neurological and cutaneous findings has a common aetiology and represents a novel recognisable entity. Because of the unusual dermatological findings, we suggest the term dyschromatosis ptychotropica. Recognition of further cases may help elucidate the aetiology of this condition and give insight into the pathophysiology of both pigmentation disorders and epileptic encephalopathies.